Zdalna edukacja - ku innowacji czy zagrożeniu? - Waszkiewicz, Izabela; Bryk, Dominika (Wydawnictwo Politechniki Łódzkiej, 2022)
This paper discusses the results of a study conducted during the Sars-CoV-2 pandemic. The study aimed to reveal individual experiences of remote education from the perspective of students and teachers. Three areas of individual functioning were discussed, the social area, the educational area and the individual area, which were based on the philosophy of the decahedron of education. In the social area, three processes were discussed: globalisation, collectivisation, and socialisation. The next part analyses the process of educating and humanising the individual, showing the transformations in the course of classes and the school environment, as well as the manifestations of the phenomenon of the hidden curriculum. The individual area covered the problem of individual development in the face of remote education and social isolation.
Remote Education – Towards Innovation or a Threat?
Keywords: remote education; Sars-CoV-2 pandemic; process of education; edukacja zdalna; pandemia Sars-CoV-2; proces edukacji